2012
DOI: 10.1063/1.4773245
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity and fast response and recovery times in a ZnO nanorod array/p-Si self-powered ultraviolet detector

Abstract: High quality, vertically aligned ZnO nanorods were grown on a silicon substrate, using microwave-assisted chemical bath deposition with poly (vinyl alcohol)-Zn(OH)2 nanocomposites as seed layer. The structure and surface morphology of the prepared ZnO nanorod arrays were characterized using X-ray diffraction and scanning electron microscopy. The optical properties were assessed using photoluminescence measurements; the results showed a high-intensity UV peak, and a lower intensity, broader visible peak. Upon e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(40 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…The latter generally fixes the pH of the solution at around 6 [16], yielding hydroxyl ions which react with Al to form Al(OH) 4 -. It is now well established that the binding of Al(OH) 4 -to the Zn 2+ terminated surfaces is essential for blocking ZnO growth along the (0001) direction and promoting lateral growth [2,11,12]. With Al wafer and equimolar solution of Zinc nitrate hexahydrate (ZN) and HMTA, Ye et al demonstrated that by increasing pH from 6 to 12 (with ammonium hydroxide, AH), thinner nanowalls could be obtained.…”
Section: Introductionmentioning
confidence: 97%
“…The latter generally fixes the pH of the solution at around 6 [16], yielding hydroxyl ions which react with Al to form Al(OH) 4 -. It is now well established that the binding of Al(OH) 4 -to the Zn 2+ terminated surfaces is essential for blocking ZnO growth along the (0001) direction and promoting lateral growth [2,11,12]. With Al wafer and equimolar solution of Zinc nitrate hexahydrate (ZN) and HMTA, Ye et al demonstrated that by increasing pH from 6 to 12 (with ammonium hydroxide, AH), thinner nanowalls could be obtained.…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3][4][5][6][7][8][9][10][11][12] This is due to both ZnO peculiar properties 13 -large and direct band gap energy of 3.3 eV, high exciton binding energy of 60 meV, high electron mobility, large piezoelectric response -and the attractiveness of synthesizing ZnO NRs via low cost methods based on solution phase growth. Among the bottom-up approaches, solution phase growth methods for nanostructures receive large attention as they ensure high deposition rates on a large variety of substrate, without the need for high temperature or vacuum systems.…”
Section: Introductionmentioning
confidence: 98%
“…The obtained m value between 0.5 and 1 suggests the presence of continuous distribution of trap levels [25,26]. The sensitivity (S) of the diode having 0.03 GO content was determined by the following relation [27].…”
Section: Resultsmentioning
confidence: 99%